2012
DOI: 10.1007/s00705-012-1331-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological study of hepatitis B virus in blood donors from five Chinese blood centers

Abstract: Although the genetic variability of hepatitis B virus (HBV) in HBV-infected patients has been extensively studied, reports on genotypes, subtypes and mutations in the S region of HBV strains from Chinese blood donors are limited. In this study, 245 blood samples from HBsAg-positive blood donors were collected from five geographically diverse blood centers in China. The S region of HBV was amplified, and the HBV genotype and subtype were determined. The amino acid sequences of the S region were aligned, and mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
2
12
2
Order By: Relevance
“…Phylogenetic analysis showed that five of them were infected with Genotype B HBV, one was Genotype C, and one was Genotype D, with Genotype B being more prevalent than Genotype C in OBI blood donors. This was consistent with the distribution of Genotypes B and C in HBV‐infected blood donors in China reported by other studies . However, accurate estimate of the prevalence of HBV genotype in OBI donors in Dehong should be further evaluated with a larger sample size.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Phylogenetic analysis showed that five of them were infected with Genotype B HBV, one was Genotype C, and one was Genotype D, with Genotype B being more prevalent than Genotype C in OBI blood donors. This was consistent with the distribution of Genotypes B and C in HBV‐infected blood donors in China reported by other studies . However, accurate estimate of the prevalence of HBV genotype in OBI donors in Dehong should be further evaluated with a larger sample size.…”
Section: Discussioncontrasting
confidence: 70%
“…However, the G145R mutation was not observed in this study while mutations of P142L, I110M, T126A, T131N, and T125M were observed, which were in or near the MHR region and may be related to the false‐negative result of HBsAg assay. In this study, approximately 57.1% (4/7) of the samples had mutations, higher than those reported by other studies in China (17%), Japan (40%), Korea (50%), France (28%), and Spain (40%) . Such a difference may be related to the different sample size, different prevalence of HBV, and different types of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations